ASSESSMENT OF THE CRITICAL CARE NURSING COMPETENCY FOR PATIENT SAFETY IN ICU SETTING - ANAS, M; SADDIQUE, H; TASNEEM, SS (Biological and Clinical Sciences Research Journal, 2024)
Critical care nursing competencies are vital for ensuring patient safety in ICU settings. This study aimed to assess the knowledge, attitudes, and practices of nurses regarding critical care competencies in a tertiary care hospital in Lahore, Pakistan. Methods: A descriptive cross-sectional study was conducted among 133 ICU nurses. Data were collected using a validated questionnaire assessing competencies in preparation, patient assessment, communication, role recognition, and organization. Descriptive and inferential statistics were used to analyze the data. Results: The majority of nurses demonstrated high competency in preparation (87.2%), patient assessment (82.0%), and equitable care (88.0%). However, gaps were observed in the documentation of communication with patients’ families and consistent adherence to documentation protocols. Nurses with higher qualifications (Post RN and BSN) and more clinical experience performed significantly better than their counterparts. Conclusion: The study identifies key strengths and gaps in critical care nursing competencies. Targeted interventions, including structured training programs and the implementation of standardized protocols, are recommended to enhance competency levels and ensure patient safety in ICU settings.